Arab Donors Respond Favorably to the Global Financial Crisis - Rouis, Mustapha (World Bank, Washington, DC, 2012)
The World Bank's 2010 study, Arab Development Assistance: four decades of cooperation, showed that Arab countries have been generous donors over the years, particularly the three Gulf countries - Kuwait, Saudi Arabia, and the United Arab Emirates (UAE) which represent over 90 percent of total Arab aid provided by those countries on which information is available. This paper confirms that the generosity extends to the period of the global financial and economic crisis. Arab Gulf countries and regional financial institutions were responsive to this new reality and collectively scaled up financial assistance to address critical development and humanitarian needs in developing countries.